2011
DOI: 10.3748/wjg.v17.i44.4899
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and management of Fasciola hepatica infection: Single-center experience

Abstract: Fasciola hepatica infection should be considered in the differential diagnosis of patients with hepatic or biliary disease and/or acute pancreatitis associated with eosinophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 16 publications
4
69
1
9
Order By: Relevance
“…Acute symptoms are caused by the tissue destruction and acute inflammation associated with larval migration through intestine, peritoneum and liver parenchyma, as well as a generalised allergic reactions to parasite antigens (5) . Fever and abdominal pain (which may be excruciating), are the most frequently reported symptoms (5,77). Anorexia, flatulence, nausea, diarrhoea, urticaria and cough are also common.…”
Section: Fascioliasismentioning
confidence: 99%
“…Acute symptoms are caused by the tissue destruction and acute inflammation associated with larval migration through intestine, peritoneum and liver parenchyma, as well as a generalised allergic reactions to parasite antigens (5) . Fever and abdominal pain (which may be excruciating), are the most frequently reported symptoms (5,77). Anorexia, flatulence, nausea, diarrhoea, urticaria and cough are also common.…”
Section: Fascioliasismentioning
confidence: 99%
“…In patients admitted in the biliary phase, abdominal pain, pain in the upper right quadrant, biliary colic, jaundice associated with the obstruction of bile ducts by the adult parasite, and inflammatory response were the most common complaints [18]. In this phase, serum ALP, GGT, and total bilirubin values were elevated, consistent with cholestasis [19].…”
Section: Discussionmentioning
confidence: 72%
“…ERCP and sphincterotomy are used to extract parasites from the biliary tree [23]. In the literature, it was reported that patients in the biliary phase may admit to the hospital due to acute pancreatitis as well [18]. In our three patients who had a diagnosis of biliary phase fascioliasis, parasites were seen and extracted with ERCP after USG; abdominal CAT was not performed.…”
Section: Discussionmentioning
confidence: 93%
“…We suspect that many of the children with eosinophilia may have had acute or chronic Fasciola infection. 24,25 Testing of one stool specimen probably limited our ability to detect low-intensity infections. Furthermore, Marcos and others 13 described a strong association between eosinophil counts and Fasciola infection in highly endemic areas.…”
Section: Discussionmentioning
confidence: 99%